2004
DOI: 10.1128/cdli.11.3.463-472.2004
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliandStaphylococcus aureusElicit Differential Innate Immune Responses following Intramammary Infection

Abstract: Staphylococcus aureus and Escherichia coli are among the most prevalent species of gram-positive and gram-negative bacteria, respectively, that induce clinical mastitis. The innate immune system comprises the immediate host defense mechanisms to protect against infection and contributes to the initial detection of and proinflammatory response to infectious pathogens. The objective of the present study was to characterize the different innate immune responses to experimental intramammary infection with E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
432
4
22

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 423 publications
(523 citation statements)
references
References 67 publications
54
432
4
22
Order By: Relevance
“…Possibly, in these sows there may be abundant and regulated release of anti-inflammatory mediators [40,53], limiting the production of the inflammatory cytokines. However, in accordance with our results, previous studies in cows have shown a significant increase in the proinflammatory cytokines at the level of both mRNA [33,37] and protein [6,11,26,32,45,48,54] in either mammary tissues or milk collected from the infected glands following intramammary inoculation with E. coli. The results here indicate that the development of clinical symptoms of coliform mastitis in the sow is associated with a locally increased proinflammatory cytokine production in response to intramammary E. coli infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Possibly, in these sows there may be abundant and regulated release of anti-inflammatory mediators [40,53], limiting the production of the inflammatory cytokines. However, in accordance with our results, previous studies in cows have shown a significant increase in the proinflammatory cytokines at the level of both mRNA [33,37] and protein [6,11,26,32,45,48,54] in either mammary tissues or milk collected from the infected glands following intramammary inoculation with E. coli. The results here indicate that the development of clinical symptoms of coliform mastitis in the sow is associated with a locally increased proinflammatory cytokine production in response to intramammary E. coli infection.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, it has been established that IL-1β, IL-6, IL-8, and TNF-α play a role in the initiation of the inflammatory responses following intramammary inoculation with Escherichia coli [6,45,48,59]. Analyses of biopsies collected from mammary glands of sows inoculated with E. coli demonstrated the transcription of the genes for a number of proinflammatory cytokines, but analyses of IL-6 and TNF-α in the same set of sows revealed that variations in serum/plasma concentrations were not reflected in the mRNA expression in mammary tissues [59,60].…”
Section: Introductionmentioning
confidence: 99%
“…Each one received at time zero RPMI in one quarter, 10 g LTA in another one, and 100 g LTA in a third quarter. The infused quarters were aseptically sampled just before infusion after the morning milking, then 4,8,12,16,24,32,48,72 and 96 h post-infusion. At each sampling time up to 24 h post-infusion, the rectal temperature was taken and a clinical examination was performed (appearance of gland and milk).…”
Section: Experimental Designmentioning
confidence: 99%
“…Milk somatic cells were counted on an automated cell counter (Fossomatic model 90; Foss Food Technology, Hillerod, Denmark) as described [4]. For the determination of the proportion of neutrophils among milk somatic cells, cytospin slides were prepared with a cytocentrifuge (Shandon Southern centrifuge, Shandon Inc, Pittsburgh, PA, USA).…”
Section: Determination Of Milk Scc and Proportion Of Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation